Rikkunshito as a Therapeautic Agent for Functional Dyspepsia and its Prokinetic and Non-Prokinetic Effects - Inokuchi, Kazumi; Masaoka, Tatsuhiro; Kanai, Takanori (Frontiers in Pharmacology, 2021)
Prokinetics is one of the therapeutic agents for functional and motility disorders of the stomach. However, its efficacy is limited. Kampo medicine is a unique medical system that was developed in Japan. In Kampo medicine, herbal medicine is prescribed based on the patient’s condition. Therefore, even for functional and motility disorders of the stomach, some herbal medicines are considered as a therapeutic option. Recently, evidence for the efficacy or the mechanism of herbal medicine for functional and motility disorders of the stomach is accumulating. Among these, rikkunshito is a well-studied herbal medicine that could be used as an alternative to prokinetics. In this review, we discuss the possibilities of herbal medicine as non-prokinetic treatments for functional and motility disorders of the stomach and provide an overview of their current use with a focus on their therapeutic mechanism.